FAKTOR-FAKTOR YANG MEMENGARUHI PERMINTAAN KUBIS DI PASAR TRADISIONAL INPRES MANONDA KOTA PALU - Inge Anggraini; Arifuddin Lamusa; Nurmedika Nurmedika (Fakultas Pertanian, Universitas Tadulako, 2022)
This study aimed to determine the effect of cabbage price, substitute goods price, consumer income, and family dependent number on the demand for cabbage in Palu City. The research was conducted at the Inpres Manonda Traditional Market of Palu City in May – July 2021. Respondents of 30 cabbage consumers was determined using the Accidental Sampling method. This research used the Multiple Linear Regression analysis. The results showed that simultaneously the price of cabbage, the price of substitute goods, the consumer income and the number of dependents had a significant effect on the demand for the cabbage at the Inpres Manonda Traditional Market. The t test showed that partially such variables as the price of the cabbage and the number of dependents had a significant effect on the demand for cabbage at the Inpres Manonda Traditional Market, while the price of substitute goods and the amount of income had not.